2012
DOI: 10.1002/clc.21976
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Revascularization in Women

Abstract: Historically, mortality rates have been higher in women than in men for both PCI and CABG. Recent registries and studies have shown that women have mortality rates similar to men after correcting for age and comorbidities. The gender gap is narrowing with respect to outcomes for women with both PCI and CABG. Revascularization with PCI and CABG in women with stable angina (SA), unstable angina (UA), non ST-elevation myocardial infarction (NSTEMI), and ST-elevation myocardial infarction (STEMI) will all be revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…However, while appreciating the risk of microvascular CAD in women, it is also important to remember that a substantial proportion of women with ACS symptoms do have male-pattern obstructive CAD (Gulati et al, 2012), so it can be argued that the frequent decision not to refer women for angiography means that their underlying coronary anatomy is not assessed and that opportunities to revascularize eligible women may be missed (Banks, 2008). Recent systematic reviews have confirmed the benefit of an early invasive therapy in women with ACS, while noting the under-representation of women in many trials and the problem of limited reporting of results by gender (Dolor et al, 2012;Lundberg & King, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, while appreciating the risk of microvascular CAD in women, it is also important to remember that a substantial proportion of women with ACS symptoms do have male-pattern obstructive CAD (Gulati et al, 2012), so it can be argued that the frequent decision not to refer women for angiography means that their underlying coronary anatomy is not assessed and that opportunities to revascularize eligible women may be missed (Banks, 2008). Recent systematic reviews have confirmed the benefit of an early invasive therapy in women with ACS, while noting the under-representation of women in many trials and the problem of limited reporting of results by gender (Dolor et al, 2012;Lundberg & King, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have noted an increased number of baseline comorbidities in women when compared to men. 1,2,5 The BMC2 (Blue Cross Blue Shield of Michigan Cardiovascular Consortium) study 22 included 22 725 patients with normal renal function and showed that, despite an increased baseline comorbidity profile, 5-year outcomes were similar. Our finding of an increased baseline comorbidity profile in the ESRD cohort should not be surprising.…”
Section: Discussionmentioning
confidence: 99%
“…Advancing age and an increase in the number of baseline comorbidities have been noted in women with normal renal function referred for coronary revascularization by PCI or CABG . Whether this differential comorbidity profile between men and women explains the variations in outcomes in patients with ESRD is still under debate . More gender‐specific research is needed …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, data on sex differences in clinical outcomes after CABG are controversial, and there have been limited data focusing on long-term outcomes. Several studies reported that women suffering from coronary heart disease tend to have more co-morbidities and are more likely to present with a severe form of cardiogenic shock that requires urgent or emergent CABG compared with men [ 3 – 5 ]. Moreover, women have relatively small body surface area, and thus smaller coronary vessels.…”
Section: Introductionmentioning
confidence: 99%